Proposals for the creation and management of geoparks in Peru - Zavala Carrión, Bilberto Luis (2015)
Since 2006 the Geological Mining and Metallurgical Institute of Peru (INGEMMET) has made an inventory and and mapped the distribution of unique geological sites that could be considered as geological heritage. the priotities of this activity are the conservation and enhancement of sites for scientific research, and importantly, the enhancement of geo-education and geotourism. Seven areas of the country have been evaluated: Marcahuasi, Lima (2006); Andagua Volcanoes Valley (2008) and Colca and Cotahuasi canyons in Arequipa (2011-2012); Protected Natural Areas (PNA) like Paracas (2007) in Ica, and Huayllay (2009) located in the center of the country. Also, an inventory of geological and mining heritage in the Puno region, with emphasis in the Tinajani Canyon was made 2013-2014. Outreach has been given with the publication of two geotouristic guides (two more in press) presented at geology conference and presentations to tourism and PNA institutions, regional and municipal governments, Peruvian Ministry of Culture, schools and school fairs, etc. Internationally, the advances have been presented in "Cities on Volcanoes, Cov 6" (Tenerife, 2010), "Regional Workshop on Geoparks" (Uruguay, 2011), II Brazilian Symposium of Geological Heritage and Geotourism (2013) and a recent Workshop in Mexico (2015), featuring the first Peruvian proposal of geopark to UNESCO. Diffusion, awareness and training are necessary to keep this geo-heritage, enhance local capabilities for geotourism and assist in the management and consolidation of geoparks. Working in different socio-economic contexts, INGEMMET acts as technical-scientific advisory entity for those with the political power to accept these proposals (communities, municipalities, associations, private owners, PNA),. The "First Symposium on Geoparks, Geotourism and Geological Heritage" organized by INGEMMET with Colca Autonomous Authority, the Regional Government of Arequipa and Caylloma and Castilla provincial municipalities unveiled new strategies of sustainable, economic and social development and the philosophy of Geoparks with emphasis on the creation of "Colca Canyon and Valley of the volcanoes Andagua Geopark". We now find an urgent need to train more geologists who can specialize in geology, in relation to geo-heritage management.